Can volumetric analysis of the brain help diagnose isolated optic neuritis? - Sayın Şakul, Ayşe Arzu; Pençe, Kadriye Betül; Örmeci, Tuğrul; Günal, Mehmet Yalçın (Wiley, 2023)
Isolated optic neuritis is a single episode inflammatory optic neuropathy. This condition, which affects the optimal function of the optic nerve, is not associated with neurological or systemic diseases. Our study aimed to compare patients with isolated optic neuritis and normal healthy individuals in terms of the cerebrum, cerebellum and hippocampus volumes by using the "volBrain Online MRI Brain Volumetry System" program. Persons diagnosed with isolated optic neuritis (n = 16) and persons without any disease (n = 16) were included in the study. VolBrain was used to process the MRI data and, the findings were compared with Mann-Whitney U test. Values with a p-value <0.05 were considered statistically significant. The cerebrum white matter volumes in the total brain and in the right-left hemispheres of the brain were statistically significantly lower in the optic neuritis group (p = 0.029; p = 0.050; p = 0.029, respectively). In the segmental cerebellum analysis, the left side lobule VIIIB, the total and right-left side lobule IX volumes were statistically significantly higher (p = 0.022; p = 0.014; p = 0.029; p = 0.018, respectively). In total, lobule I-II volume was statistically significantly lower in the optic neuritis group (p = 0.046). In the segmental hippocampus analysis, the right side CA2-CA3, the total and right-left side SR-SL-SM volumes were statistically significantly lower in the optic neuritis group (p = 0.039; p = 0.050; p = 0.016, respectively). There are neurodegenerative changes in brain volume in patients with isolated optic neuritis. Although volBrain alone is not sufficient to diagnose isolated optic neuritis, it provides quantitative data that can be used as a complementary diagnostic method.
Keywords: Automatic Segmentation; Brain Atrophy; Diagnostic Imaging; Isolated Optic Neuritis; Volumetricanalyses